Managing Matajoosh: determinants of first Nations' cancer care decisions. Issue 1 (December 2016) - Lavoie, Josée; Kaufert, Joseph; Browne, Annette; O'Neil, John
Abstract Background Accessing cancer treatment requires First Nation peoples living in rural and remote communities to either commute to care, or to relocate to an urban centre for the length or part of the treatment. While Canadians living in rural and remote communities must often make difficult decisions following a cancer diagnosis, such decisions are further complicated by the unique policy and socio-historical contexts affecting many First Nation peoples in Canada. These contexts often intersect with negative healthcare experiences which can be related to jurisdictional confusion encountered when seeking care. Given the rising incidence of cancer within First Nation populations, there is a growing potential for negative health outcomes. Methods The analysis presented in this paper focuses on the experience of First Nation peoples' access to cancer care in the province of Manitoba. We analyzed policy documents and government websites; interviewed individuals who have experienced relocation (N = 5), family members (N = 8), healthcare providers and administrators (N = 15). Results Although the healthcare providers (social workers, physicians, nurses, patient navigators, and administrators) we interviewed wanted to assist patients and their families, the focus of care remained informed by patients' clinical reality, without recognition of the context which impacts and constrains access to cancer care services. Contrasting and converging narratives identify barriers to early diagnosis, poor coordination of care across jurisdictions and logistic complexities that result in fatigue and undermine adherence. Providers and decision-makers who were aware of this broader context were not empowered to address system's limitations. Conclusions We argue that a whole system's approach is required in order to address these limitations.